Sirt5 Inhibits BmNPV Replication by Promoting a Relish-Mediated Antiviral Pathway in Bombyx mori - Zhang, Mengmeng; Fei, Shigang; Xia, Junming; Wang, Yeyuan; Wu, Hongyun; Li, Xian; Guo, Yiyao; Swevers, Luc; Sun, Jingchen; Feng, Min (Frontiers in Immunology, 2022)
Silent information regulators (Sirtuins) belong to the family of nicotinamide adenine dinucleotide (NAD+)-dependent histone deacetylases (HDACs) that have diverse functions in cells. Mammalian Sirtuins have seven isoforms (Sirt1–7) which have been found to play a role in viral replication. However, Sirtuin members of insects are very different from mammals, and the function of insect Sirtuins in regulating virus replication is unclear. The silkworm, Bombyx mori, as a model species of Lepidoptera, is also an important economical insect. B. mori nucleopolyhedrovirus (BmNPV) is a major pathogen that specifically infects silkworms and causes serious losses in the sericulture industry. Here, we used the infection of the silkworm by BmNPV as a model to explore the effect of Sirtuins on virus replication. We initially knocked down all silkworm Sirtuins, and then infected with BmNPV to analyze its replication. Sirt2 and Sirt5 were found to have potential antiviral functions in the silkworm. We further confirmed the antiviral function of silkworm Sirt5 through its effects on viral titers during both knockdown and overexpression experiments. Additionally, Suramin, a Sirt5 inhibitor, was found to promote BmNPV replication. In terms of molecular mechanism, it was found that silkworm Sirt5 might promote the immune pathway mediated by Relish, thereby enhancing the host antiviral response. This study is the first to explore the role of Sirtuins in insect-virus interactions, providing new insights into the functional role of members of the insect Sirtuin family.